Cosmic justice between theory and practice in John Rawls’ philosophy - Boussekek, Abdelghani (Journal of Humanities & Social Sciences, 2023)
Justice is one of the most important human virtues that a person should have, as he is a moral and ethical being as well as a social and even universal value. Before it, injustice and hatred will disappear, and peace, love, brotherhood and tolerance prevail, and among the theories that have emerged, the theory of justice by the American philosopher John Rawls, who proposed the idea of universal justice It is justice between peoples and nations that is built according to new foundations and principles that serve as a starting point for building new social and political systems, and from there building a new society in order to realize the dream of mankind and humanity in reaching effective justice in which inequality and injustice will disappear and universal justice is achieved on the ground. That is why the aim of this article was to show how justice can be achieved among peoples, and how we can build social justice within society and between peoples, and therefore we will follow the critical analytical approach to discuss these ideas, in order to reach the desired results, including the possibility of applying the foundations and principles of global justice. As for the recommendations that we can make, they are that justice is a moral virtue and one of the principles upon which societies are built. Rawls also recommends that justice be applied within and between societies according to a just law.